2015
DOI: 10.1101/030361
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Human Microbiota of the Argentine Population- A pilot study

Abstract: Here we present the first dataset based on human microbiota samples of an urban middle-income population in South America. We characterized the microbiota of six different body habitats: palatine tonsils, saliva, buccal mucosa, throat, anterior nares and gut from samples of healthy individual living in a metropolitan area in Argentina. Our initial findings revealed differences in the structure and composition of the microbial communities compared to the US urban population. By sharing our data, we want to acti… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
(10 reference statements)
0
4
0
Order By: Relevance
“…For instance, Firmicutes are decreased but Bacteroidetes have no changes in Colombian adults compared with Americans, Europeans and Asians (Escobar et al 2014;Magne et al 2016). Moreover, Ruminococcaceae, Lachnospiraceae, Rikenellaceae and Prevotellaceae are more abundant in Argentinan than Americans (Carbonetto et al 2016;Hansen et al 2019).…”
Section: Geographical Locationmentioning
confidence: 96%
“…For instance, Firmicutes are decreased but Bacteroidetes have no changes in Colombian adults compared with Americans, Europeans and Asians (Escobar et al 2014;Magne et al 2016). Moreover, Ruminococcaceae, Lachnospiraceae, Rikenellaceae and Prevotellaceae are more abundant in Argentinan than Americans (Carbonetto et al 2016;Hansen et al 2019).…”
Section: Geographical Locationmentioning
confidence: 96%
“…Overall, 25 cases and 25 controls (wo-HCC) were well matched according to those variables previously described and were included in the final assessement of gut microbiome (Figure 1). A subgroup of 25 healthy individuals were also enrolled, matched according to gender in a 1:1 ratio 26 . Baseline patient characteristics are shown on Table 1.…”
Section: Participating Patients Characteristicsmentioning
confidence: 99%
“…In particular only three articles have been published studying the gut microbiome of different Argentine populations, two of them of our authorship. The first local pilot study reported the most relevant and abundant bacteria in samples from different body regions in individuals from Rosario, Santa Fe (Argentina) [21] . We recently published the microbial gut diversity of Buenos Aires (BA), being the first local report in this area [22] .…”
Section: Introductionmentioning
confidence: 99%